2013
DOI: 10.1016/j.pupt.2012.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Novel low molecular weight lignins as potential anti-emphysema agents: In vitro triple inhibitory activity against elastase, oxidation and inflammation

Abstract: No molecule has been found to be effective against emphysema to date primarily because of its complex pathogenesis that involves elastolysis, oxidation and inflammation. We here describe novel unsulfated or sulfated low molecular weight lignins (LMWLs) chemo-enzymatically prepared from 4-hydroxycinnamic acids monomers, as the first potent triple-action inhibitors of neutrophil elastase, oxidation and inflammation. The inhibitory potencies of three different cinnamic acid-based LMWLs were determined in vitro us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Thus, direct inhibition of neutrophil elastase and plasmin‐mediated indirect inhibition of MMPs could represent a novel therapy for chronic obstructive pulmonary diseases. This was recently demonstrated by Saluja et al in an in vitro antiemphysema study of sulfated LMWLs …”
Section: Plasmin Inhibitors As Antifibrinolyticssupporting
confidence: 52%
See 1 more Smart Citation
“…Thus, direct inhibition of neutrophil elastase and plasmin‐mediated indirect inhibition of MMPs could represent a novel therapy for chronic obstructive pulmonary diseases. This was recently demonstrated by Saluja et al in an in vitro antiemphysema study of sulfated LMWLs …”
Section: Plasmin Inhibitors As Antifibrinolyticssupporting
confidence: 52%
“…This was recently demonstrated by Saluja et al in an in vitro antiemphysema study of sulfated LMWLs. 255…”
Section: Sulfated Low Molecular Weight Lignins (Lmwls)mentioning
confidence: 99%
“…The decrease of oxidative and inflammatory damage to the kidney in streptozotocin-induced diabetic rats due to lignin-derived lignophenols was reported by Sato et al [ 51 ]. Similar to these results, low molecular weight lignins were tested regarding their potential as anti-emphysema agents in vitro [ 52 ].…”
Section: Lignin Antioxidant Capacity and Bioactivitymentioning
confidence: 92%
“…13 Additionally, the study from Baurhoo et al demonstrated that purified lignin with low molecular weight monophenolic fragments had preferable antimicrobial properties against pathogenic bacteria and could potentially be considered as a natural feed additive. 21 Therefore, an hypothesis is derived here that the heterogeneity of lignin including the polydispersity of molecular weight and the content of functional groups may result in differences in antimicrobial activities. 16,17 The heterogeneity of lignin evidently results in the inhomogeneous structures and properties of lignin.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Because the phenolic hydroxyl group is a crucial factor for the free radical scavenging of lignin, low molecular weight lignin showed preferable antioxidant properties 19 and antioxidation-relative bioactivities, such as reducing carbon tetrachloride-induced toxicity 20 and inhibitory activity against inflammation. 21 Therefore, an hypothesis is derived here that the heterogeneity of lignin including the polydispersity of molecular weight and the content of functional groups may result in differences in antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%